MOGOK KERJA SEBAGAI UPAYA MEWUJUDKAN HAK BURUH - -, Sunarno (Universitas Slamet Riyadi, 2008)
Abstract : The working strike is the basic right of worker. Therefore, everyone can not stop implementing his right. If anyone is against this regulation, so can be punished.This right is implemented in according to regulation specially UU Nomor 13 Tahun 2003 and Kepmenakertrans Nomor: Kep-232/Men/2003 in order to evaluate as a legal working strike.The working stike can only be implemented at the certain factory, and there are no time’s regulation to implement working strike. Key words: The working strike and to implement